Colorectal endometriosis: Five years' experience in this enigmatic problem. Issue 3 (August 2017) - Ofkeli, Ozcem; Ulas, Murat; Oter, Volkan; Aksoy, Erol; Zengin, Neslihan; Ozer, Ilter; Bostanci, Erdal Birol
Abstract : Aim: Endometriosis primarily affects women of reproductive age, and is responsible for impairing their quality of life. The presence of severe symptoms, including stenosis of the intestinal lumen, diagnostic difficulty (suspicion of malignancy) and intolerance to hormonal therapy, are indications for surgery. Despite numerous studies on endometriosis, there is still considerable controversy about its incidence, pathogenesis, diagnosis and optimal treatment. Patients and methods: The present retrospective, observational study included 11 patients diagnosed with intestinal endometriosis between January 2009 and December 2013. Demographic data, clinical presentation, diagnostic modalities, localization of the disease and intraoperative data were collected. Results: The median age of the patients was 43 years (34–63 years). Eight patients had intermittent abdominal pain, seven had change in bowel habits and three had rectal bleeding. Seven patients were operated on for severe stenosis of the intestinal lumen (intestinal obstruction), and three for a suspected malignancy. Postoperatively, all of the patients who underwent resection were free of pain. No patient had any disease recurrence on abdominal ultrasonography or computed tomography images. Conclusion: Intestinal endometriosis should be considered in female patients of reproductive age presenting with constipation, rectal bleeding and abdominal pain. Repeated inadequate biopsies should also raise suspicion of intestinal endometriosis. Intestinal endometriosis is a rare disease with diagnostic difficulties, and despite medical management, treatment option is usually surgery. However, in patients diagnosed preoperatively with no intestinal obstruction, medical therapy can be tried.